Investigating the effects of seismic isolators on steel asymmetric structures considering soil-structure interaction. (October 2020) - Radkia, Sahar; Rahnavard, Rohola; Tuwair, Hesham; Abbas Gandomkar, Farhad; Napolitano, Rebecca
Abstract: Building isolation is a practical and ubiquitous method for reducing inter-story drift and story acceleration. Previously it has been shown that since an isolator can increase the time period and damping, it can decrease the total energy transmitted from the ground to the structure. The main purpose of this study was to investigate the behavior of asymmetric sliding buildings with steel moment frame systems subject to earthquake loading (both horizontal and vertical), while taking into account the effects of soil-structure interaction. A total of 24 three-dimensional structural models, including a single-story structure (40% irregularity), a five-story structure (regularity, 20%, 40% and 60% irregularity) and a ten-story structure (40% irregular) were dynamically analyzed using nonlinear finite element analysis. The results of this study indicated that, in terms of inter-story drift and story accelerations, seismic isolation had a significant impact on the dynamic responses of structures. This effect was more pronounced in single-story structures than in others. Additionally, the results showed that structural irregularities did not affect the dynamic response of the structure, including the displacement and acceleration of the stories. Furthermore, this study showed that when soil is converted from type II to types III and IV, the displacement and slipping speed decreased for all studied structures. Lastly, the results suggested that substructure soil typology had a significant effect on the design parameters of isolators.